Short- and long-term reliability of heart rate variability indices during repetitive low-force work - Hallman, D.; Srinivasan, D.; Mathiassen, Svend (Springer-Verlag, 2015)
© 2014, Springer-Verlag Berlin Heidelberg. Purpose: Heart rate variability (HRV) is often monitored in occupational studies as a measure of cardiac autonomic activation, but the reliability of commonly used HRV indices is poorly understood. In the present study, we determined the variability between and within subjects of common HRV indices during a repetitive low-force occupational task, i.e., pipetting, and interpreted the results in terms of necessary sample sizes in studies comparing HRV between conditions or groups. Methods: Fourteen healthy female subjects performed a standardized pipetting task in the laboratory on three separate days within a short-time span ( < 2 weeks), and on one additional occasion 6 months later. A number of standard HRV indices were calculated in both time and frequency domains. For each HRV index, variance components were estimated between subjects, within subjects between occasions far apart in time, and within subjects between days within a 2-week period. Results: We found that the time interval between repeated measurements did not influence the extent of HRV variability, and that the reliability of the most HRV indices was sufficient for even small study samples (30 subjects or less) to be able to detect, with satisfying power ( > 0.80), a significant 10 to 20 % difference in HRV between groups, and between conditions within individuals. Conclusions: We conclude that HRV can be used as a reliable and feasible marker of autonomic activity in occupational studies of repetitive low-force work.